La Prueba de Admisión a la Universidad y Sus Efectos Psicosociales en los Estudiantes desde el Enfoque de Trabajo Social - Benítez Alulima, Andrea Katherine (2016)
This research in the educational unit Bernardo Valdivieso city of Loja; It is based on the analysis of the psychosocial effects caused by the test for admission to college, then to not see their dreams crystallized drop out leaving aside their goals. This process had a critical inquiry of analysis to be a topical issue and concern for close to completing his secondary education students. That is why during the course of the investigation, the objectives aim to improve the attitude of students and avoid the psychosocial effects upon determining causes and effects that causes the admission test. During the investigative process different findings were found, among which highlights students when taking the exam for admission feel, academic stress, due to the process being made for admission to higher education, which represents a great pressure them, generating serious psychosocial problems such as anxiety, frustration, depression, disappointment, sadness. In addition to parents it becomes an alarming situation, why, their desire is to see that their children continue their studies and to have access to college. The methodology is based on a quantitative and qualitative study, which surveys was established 50 students, interviews with parents and teachers, thus covering, the educational trilogy of the institution, allowing to determine cause and effect in relation to the object of study . Within the qualitative analysis of the data obtained; it could study and detail the overall summary of the results achieved, thereby enabling justify the problem posed at the beginning of the project, and also build a proposal directed to counter this problem through training and prevention.